How the Signaling Crosstalk of B Cell Receptor (BCR) and Co-Receptors Regulates Antibody Class Switch Recombination: A New Perspective of Checkpoints of BCR Signaling - Chen, Zhangguo; Wang, Jing H. (Frontiers in Immunology, 2021)
Mature B cells express B cell antigen receptor (BCR), toll-like receptors (TLR) and TNF family receptors including CD40 and B-cell activating factor receptor (BAFFR). These receptors transduce cellular signals to govern the physiological and pathological processes in B cells including B cell development and differentiation, survival, proliferation, and antibody-mediated immune responses as well as autoimmune diseases and B cell lymphomagenesis. Effective antibody-mediated immune responses require class switch recombination (CSR), a somatic DNA recombination event occurring at the immunoglobulin heavy chain (Igh) gene locus. Mature B cells initially express IgM as their BCR, and CSR enables the B cells to switch from expressing IgM to expressing different classes of antibodies including IgG, IgA or IgE that exhibit distinct effector functions. Here, we briefly review recent findings about how the signaling crosstalk of the BCR with TLRs, CD40 and BAFFR regulate CSR, antibody-mediate immune responses, and B cell anergy.